 # Check which of the following are solutions of the equation x-2y = 4 and which are not: (i) (0, 2) (ii) (2, 0) (iii) (4, 0) (iv) (√2, 4√2) (v) (1, 1)

(i) (0, 2)

Given: x – 2y = 4

As, x=0 and y=2

On substituting the values of x and y in the equation, we get,

x – 2y = 4

0 – (2×2) = 4

-4 ≠ 4

L.H.S ≠ R.H.S

Thus, (0, 2) is not a solution to the given equation x – 2y = 4.

(ii) (2, 0)

Given: x – 2y = 4

As, x = 2 and y = 0

On substituting the values of x and y in the equation, we get,

x – 2y = 4

2 – (2×0) = 4

2 – 0 = 4

2 ≠ 4

L.H.S ≠ R.H.S

Thus, (2, 0) is not a solution to the given equation x – 2y = 4.

(iii) (4, 0)

Given: x – 2y = 4

As, x= 4 and y=0

On substituting the values of x and y in the equation, we get,

x – 2y = 4

4 – 2×0 = 4

4 – 0 = 4

4 = 4

L.H.S = R.H.S

Thus, (4, 0) is a solution to the given equation x – 2y = 4.

(iv) (√2, 4√2)

Given: x – 2y = 4

As, x = √2 and y = 4√2

On substituting the values of x and y in the equation, we get,

x – 2y = 4

√2 – (2×4√2) = 4

√2 – 8√2 = 4

-7√2 ≠ 4

L.H.S ≠ R.H.S

Thus, (√2, 4√2) is not a solution to the given equation x – 2y = 4.

(v) (1, 1)

Given: x – 2y = 4

As, x= 1 and y= 1

On substituting the values of x and y in the equation, we get,

x – 2y = 4

1 – (2×1) = 4

1 – 2 = 4

-1 ≠ 4

L.H.S ≠ R.H.S

Thus, (1, 1) is not a solution to the given equation x – 2y = 4.